Efektivitas Metode Insya’ Muwajjah untuk Meningkatkan Maharah Kitabah dalam Pembelajaran Bahasa Arab Santriwati Kelas X Madrasah Aliyah Al-Mukmin Ngruki Sukoharjo Tahun Pelajaran 2022/2023 - Tsaqifah Ululhikmah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2022)
This research is motivated by observational data showing that many tenth-grade female students (santriwati) at Madrasah Aliyah Al-Mukmin Ngruki Sukoharjo in the 2022/2023 academic year still lack proficiency in writing Arabic. The aim of this study is to examine the implementation of the guided composition (insya’ muwajjah) method, the supporting and inhibiting factors in its application, and to determine the effectiveness of using the guided composition method to improve writing skills (maharah kitabah) in Arabic language learning. The research was conducted on tenth-grade female students at Madrasah Aliyah Al-Mukmin Ngruki Sukoharjo in the 2022/2023 academic year. The method used in this study is descriptive qualitative research. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis employed the technique stated by Miles and Huberman, which includes: data collection, data reduction, data display, and conclusion drawing or verification. The validity of the research data was examined using triangulation techniques. The research results show that the application of the guided composition method to improve the Arabic writing skills of the tenth-grade female students at Madrasah Aliyah Al-Mukmin Sukoharjo in the 2022/2023 academic year is considered good, as 80% of the students achieved scores above the minimum passing grade (KKM), and 20% achieved the minimum passing grade, which is 60.